Influence of Magnetically Treated Saline Water on Growth and Tomato Production. (Journal of Pharmaceutical Negative Results, 2023)
Salinity is one of the major environmental stresses that can inhibit plant growth, development and decreased the crop production. The aim of this study was to assess some growth parameters, yield and irrigation water use efficiency for tomato under different saline water levels. Thus; a plot experiment designed to contain three factors, First factor is dripper discharge which divided into two treatments (4Lph and 8Lph for Q1 and Q2 respectively). The second is saline water which have three treatments (S1= 2000, S2=4000 and S3=6000 ppm). Finally, the third factor is magnetic device which divide into two treatments [magnetic (M) and nonmagnetic treatments (NM)]. Results reflected that (M) magnetic treatment has a significant influence on plant length (PL) compare with (NM) non magnetic treatment where, (PL) value with (M) treatment obtained (111.27cm) but with (NM) treatment the value was (101.5cm). Saline water treatments had significant influence on Number of leaves (NL) where the highest value was obtained under S1 by (53.08) but with S3 value was (31.84). Furthermore; Magnetic water treatment (M) influence on (NL) significantly where the highest value for NL under (M) treatment was 47.6 however under (NM) was (41.21). Highest yield value corresponded with magnetic water treatment (M) by (7 Ton.Fed-1) and the lowest value was (4.4 Ton.Fed-1) with (NM) treatment. In addition, with saline water treatment data observed with highest yield value by (10.4 Ton.Fed-1) under (2000PPM) but the low significant value was recorded with (6000PPM) by average (1.9 Ton.Fed-1). On the other hand, yield obtained (6.2 Ton.Fed-1) as an average with dripper discharge (4Lph); however, the lowest yield value recorded under (8Lph) by (5.1 Ton.Fed-1). There are a positive effect for Magnetic water treatment compare with non magnetic treatment; where, the irrigation water use efficiency (IWUE) was recorded (3.28 Kg.m-3) under magnetic treatment (M) but with non magnetic treatment the value was (2.07 Kg.m-3). However; by increasing water salinity from 2000 to 4000 to 6000 PPM the IWUE decreased significantly from (5.0 to 2.13 to 0.9 Kg.m-3) respectively. Finally, Results reveal that the magnetically treated saline water has the potential to enhance yield and growth parameter under different saline water levels.